Architectural Pedagogy within the design studio: A trench between learning and teaching - Pirdavari, Mohammad (2022)
There is a structural conflict between the processes of what is being taught to students in architecture major at university, and what they really need to be taught. This might be due to the fact that in many countries, students enter the architecture field with a secondary school logical learning method. Most of the students graduate from fields such as Mathematics, which nurture different parts of the brain and create a pattern for solving problems that are completely different from what they need in the architectural design studio. The educational system is basically devised on training learners with an art-based background. Nevertheless, these art-based students also face difficulties and great challenges in comprehending their design course practices within an architecture school standard. The design problem is a multidimensional question that is entangled with various types of factors. The human mind has different layers of patterns for thinking and learning. The learning process categorizes people according to Kolbs theory into four followings: diverging, assimilating, converging, and accommodating. The different thinking styles, learning styles, and problem-solving strategies divided students into two different types of categories. It seems that the educational system doesn't have a holistic strategy for its teaching method to benefit all the categories. This paper examines the flaws in the curriculum of architectural education, which is sometimes the cause for a lack of high performance in the educational system from different perspectives. For this aim to be reached, the research examines the real abilities and disabilities of the students and the education systemŽs response. This survey has been conducted to understand the ways in which the learners perceive the courses and their performance in the academia and in their future professional practice. The outcome of this research prepares a basis for changes in the curriculum and the teaching system. This paper contributes to the architectural academic system, decision-makers, and all the academic members in architecture.